Implementation of Emergency Curriculum in Local Wisdom Contents at Television as a Learning Media During the Pandemic Period - Wiryanto Wiryanto; Suprayitno Suprayitno; M. Gita Primaniarta (Journal of Innovation in Educational and Cultural Research, 2024)
The emergency curriculum policy was implemented to anticipate students' learning difficulties during distance learning using the home learning program via television. This research aims to describe the depth of local wisdom material as thematic learning for students' knowledge. The research used a qualitative descriptive method about using learning through TELEVISION to implement emergency curriculum policies. The informants processed were two (2) teachers of a grade 4 elementary school who had previously designed learning tools based on emergency curriculum procedures. The participants in this study were fifty-nine (59) children in grade four (4). This research was conducted during a three-month pandemic in the second term of 2021. The research results explain that for each material on the topic 'Where I Live', local wisdom material was found and broadcasted for 30 minutes. The obtained result from the data of students who answered seven (7) related questions studied through television, which contained local wisdom content, was that 80.04% of students said 'yes', 15.76% gave no answer, and 6.65% said 'maybe'. Implementation of distance learning using television media requires a strong synergy between teachers, students, and parents.